Organocatalytic Ring-Opening Polymerization Strategies for Synthesis of Poly(phosphothioesters) with a Pendent Phenyl Group - Yan, Huating; Xu, Guangqiang; Yang, Rulin; Lv, Chengdong; Zhou, Li; Hao, Xin-Qi; Wang, Qinggang (Synlett, 2020)
A novel type of phosphothioester substrate, 2-phenyl-1,3,2-dioxaphospholane 2-sulfide (PTP), has been synthesized and subjected to ring-opening polymerization. DBU/thiourea served as an efficient cooperative organocatalyst for the synthesis of poly(PTP), delivering the polymer with a well-defined structure, a relatively narrow molecular-weight distribution (1.14–1.20), and high molecular weight (up to 45.2 kg/mol). The ring-opening polymerization process showed a controlled/living nature. In addition, diblock copolymers of PTP with rac-lactide with well-defined structures were also synthesized.
Keywords: organocatalysis; ring-opening polymerization; polyphosphothioesters; living polymerization; phenyldioxaphospholane sulfide; block copolymerization